Translations of new public management: a decentred approach to school governance in four OECD countries - Wilkins, A.; Collet-Sabé, J.; Gobby, Brad; Hangartner, J. (2019)
© 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group. Despite the prevalence of corporate and performative models of school governance within and across different education systems, there are various cases of uneven, hybrid expressions of New Public Management (NPM) that reveal the contingency of global patterns of rule. Adopting a ‘decentred approach’ to governance (Bevir, M. 2010. “Rethinking Governmentality: Towards Genealogies of Governance.” European Journal of Social Theory 13 (4): 423–441), this paper compares the development of NPM in four OECD countries: Australia, England, Spain, and Switzerland. A focus of the paper is how certain policy instruments are created and sustained within highly differentiated geo-political settings and through different multi-scalar actors and authorities yet modified to reflect established traditions and practices.